PtpA and PknG Proteins Secreted by Mycobacterium avium subsp. paratuberculosis are Recognized by Sera from Patients with Rheumatoid Arthritis: A Case–Control Study - Bo, Marco; Erre, Gian Luca; Bach, Horacio; Slavin, Yael N; Manchia, Piera Angela; Passiu, Giuseppe; Sechi, Leonardo A (Journal of inflammation research, 2019)
Rheumatoid arthritis (RA) can result from complex interactions between the affected person's genetic background and environment. Viral and bacterial infections may play a pathogenetic role in RA through different mechanisms of action. We aimed to evaluate the presence of antibodies (Abs) directed against two proteins of subsp. (MAP) in sera of RA subjects, which are crucial for the survival of the pathogen within macrophages. Moreover, we analyzed the correlation of immune response to both proteins with the following homologous peptides: BOLF1 , MAP_4027 and IRF5 to understand how the synergic role of Epstein-Barr virus (EBV) and MAP infection in genetically predisposed subjects may lead to a possible deregulation of interferon regulatory factor 5 (IRF5). The presence of Abs against protein tyrosine phosphatase A (PtpA) and protein kinase G (PknG) in sera from Sardinian RA patients (n=84) and healthy volunteers (HCs, n=79) was tested by indirect ELISA. RA sera showed a remarkably high frequency of reactivity against PtpA in comparison to HCs (48.8% vs 7.6%; <0.001) and lower but statistically significant responses towards PknG (27.4% vs 10.1%; =0.0054). We found a significant linear correlation between the number of swollen joints and the concentrations of antibodies against PtpA ( =0.018). Furthermore, a significant bivariate correlation between PtpA and MAP MAP_4027 peptide has been found, suggesting that MAP infection may induce a secondary immune response through cross-reaction with IRF5 (R =0.5). PtpA and PknG are strongly recognized in RA which supports the hypothesis that MAP infection may be involved in the pathogenesis of RA.